Optimal reactive power control using compensating capacitor based on artificial immune system - Razali N.S.; Roslan N.; Mansor M.H.; Musirin I.; Shaaya S.A.; Jelani S. (World Academy of Research in Science and Engineering, 2023)
This paper presents the application of compensating capacitors for optimal power flow in transmission system. The compensating capacitors are placed at suitable locations in the transmission system and the size of reactive power to be injected by the capacitors to the system is obtained using artificial immune system (AIS) optimization technique. AIS will find the best value of reactive power of the compensating capacitors so that the total system loss is minimum. It is found that applying the AIS optimization technique is prospective approach for finding optimal reactive power output of the installed compensating capacitors in controlling reactive power of transmission system. 2019, World Academy of Research in Science and Engineering. All rights reserved.